A Rare Case of Large Skull Base Meningioma Mimicking Otitis Media with Effusion. (19th December 2013) - Alzahrani, Musaed; Gaboury, Louis; Saliba, Issam
Abstract : A 48-year-old woman presented with unilateral hearing loss and tinnitus for three years associated with middle ear effusion. Previous treatments, including antibiotics, corticoids, and transtympanic tube, were ineffective. Otomicroscopy showed a greyish retrotympanic mass associated with middle ear effusion. High resolution CT scan of the mastoid was in favor of chronic oto-mastoiditis without any evidence of tegmen dehiscence. Surgical exploration revealed a polypoid greyish mass filling the tympanic cavity. Histological examination postoperatively revealed a meningothelial meningioma. Postoperative magnetic resonance imaging (MRI) was obtained and showed a large skull base meningioma, extending from the clivus anteriorly to the porus acusticus posteriorly with middle ear invasion. After discussion with the multidisciplinary tumor board, it was managed by stereotactic radiotherapy due to the high surgical associated neurovascular risks. In conclusion, middle ear meningioma, although still a rare presentation, should be suspected in the presence of atypical chronic OME.